Papillary mucinous cystadenocarcinoma: rare malignant tumor in minor salivary gland - Mariano, Ronaldo Célio; Oliveira, Marina Reis; Silva, Amanda De Carvalho; Mariano, Lúcia De Carvalho Freire; Vargas, Pablo Agustin; Almeida, Oslei Paes De (Faculdade São Leopoldo Mandic, 2016)
ABSTRACT Clinical case description of a papillary mucinous cystadenocarcinoma, extremely rare malignant tumor in the salivary gland and difficult to diagnose, in geriatric patient. Patient with 86 years old was referred for treatment with nodular lesion on the inner side of left lower lip extending to the bucal mucosa, without any clinical appearances of malignancy. The lesion was asymptomatic, had flabby consistency and slow growth. Despite the favorable clinical features, after surgical removal, was diagnosed as papillary mucinous papillary mucinous cystadenocarcinoma. Nonetheless, the cellular atypia found was considered to be mild and immunohistochemical evaluation the reaction to Ki-67 was low, indicating a low rate of proliferation of the tumor. Medical evaluation confirmed the absence of systemic disorders or distant metastases. Although it is a malignant lesion, due to low degree of proliferation of lesion and the careful follow-up carried out, there was a favorable evolution after conservative treatment in a follow-up period of 11 years and six months.

RESUMO Descrição do caso clínico de um cistadenocarcinoma papilar mucinoso, tumor maligno extremamente raro em glândula salivar e de difícil diagnóstico, em um paciente geriátrico. Paciente com 86 anos foi encaminhado para tratamento com lesão nodular na parte interna do lábio inferior do lado esquerdo estendendo-se para a mucosa jugal sem qualquer aspecto clínico de malignidade. A lesão era assintomática, apresentava consistência flácida e crescimento lento. Apesar das características clínicas favoráveis, após a remoção cirúrgica, o diagnóstico foi de cistadenocarcinoma papilar mucinoso. Entretanto, a atipia celular encontrada foi considerada leve e a reação imunohistoquímica para o Ki67 baixa, indicando uma baixa taxa de proliferação do tumor. A avaliação médica confirmou a ausência de transtornos sistêmicos e de metástases a distância. Apesar de se tratar de uma lesão maligna, devido ao baixo grau de proliferação do tumor e o acompanhamento cuidadosos realizado houve uma evolução favorável após o tratamento conservador após um período de acompanhamento de 11 anos e 6 meses.
Cistadenocarcinoma papilar mucinoso: tumor maligno raro em glândula salivar menor
Keywords: Cystadenocarcinoma; Neoplasm; Salivary gland.; Cistadenocarcinoma; Neoplasias; Glândulas salivares.